Analysis Study Proportion for Need of Labour Component on Road Development Project in Indonesia - R Arifuddin; A. F. C Putri; I R Rahim (International Association of Lowland Technology, 2021)
Infrastructure development in Indonesia continues to develop very rapidly, this development has an effect on increasing the needs of elements related to infrastructure development, one of which is manpower, need to be careful planning in the use of the number of workers according to the needs of construction activities. The research aims to model the relationship between the volume of work and the needs of workers, builders, and the number of mandors on road construction projects. The data processing on this study uses the help of Microsoft Excel programs and SPSS version 22. Data analysis techniques use simple and multiple linear regression analyses, normality tests, and correlation tests. The result of a simple regression analysis shows the influence of the number of workers, the number of foreman, and the number of successive builders of the volume of work is 15.25%, 16.31%, and 16.4%. And the results of multiple regression analysis show every improvement of the variable number of workers, the number of handyman and the number of Foreman will be followed by increased volume of work on the road construction project. Result of the results from this research can be used related government to be able to predict the number of construction workers needed to build a number of KM road.